A failure of dialogue? a critical reflection on a discussion between a teacher trainer and a pre-service second-language teacher. Issue 3 (4th May 2017) - Yagata, Katsuhide
Abstract: Reflective practice in teacher education often involves dialogic communication between teacher educators and teachers. This essay asks what constitutes authentic dialogic engagement in discussions between a pre-service second-language (SL) teacher and her university supervisor. Written as a self-critical reflection, the paper first describes the author's thoughts and feelings about a post-teaching session he conducted with one of his supervisees and identifies possible disconnections existing between them. Drawing on Mikhail Bakhtin's concept of dialogism and Hans-Georg Gadamer's of genuine dialogue, this paper reflects on the dispositions that foster a dialogic relationship between teacher educators and pre-service and in-service teachers.